The Extent Of Using The Modern Teaching Techniques In Teaching Languages of Institutes Language in Damascus And Tishreen Universities From The Teachers viewpoint In Two Universities - Ali, Kheder; Ajeeb, Yehia (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The Research aims to investigate the extent of using the modern teaching techniques in the Institutes Languages, and to investigate the important the modern of techniques in teaching the Languages in Institutes Languages of Damascus and Tishreen Universities, From The Teachers viewpoint, And know the differences in the answers to the members of the teachers according to the research variables: (University, academic specialization, years of experience). In addition to discovered the difficulties using the modern teaching techniques in teaching techniques in the Institutes Languages, and presenting the suggestions for improvement teaching techniques through of modern techniques. To achieve the objective of the research a questionnaire has been included Educational Contribution and Educational Goals which realized of using the modern teaching techniques in teaching techniques, and appreciated on (62) teachers of the Institutes Languages of Damascus and Tishreen Universities for the academic year 2014/2015. The results showed that the most the modern teaching techniques using were for sonic recorders, and the Educational Contribution which realized of using the modern teaching techniques in teaching techniques with a middle degree, and Educational Goals with a higher degree. In fact, there are no different in the answers of the teachers about Educational Contribution and Educational Goals according to the University, also according to the variables (academic specialization, years of experience) in the Educational Goals, but there are different in Educational Contribution to the variables (academic specialization, years of experience). In addition to, the most difficult in using the modern teaching techniques in teaching techniques, the students density in the classroom, and the research sample showed, design linguistic laboratories prepared with modern techniques.